The Science of the Philosophy of Right in Ayat allah Javadi Amoli’s Thoughts - Mohammad-Hoseyn Talebi (حکمت اسرا, 2015)
The most important issues in the science of the philosophy of right are the notion of right, the kinds of right, the right holders, and the origin of right. In this paper, with aids of textual research, we will try to draw the thoughts of Ayat Allah Javadi Amoli about these problems out of his writings. The below propositions are the extract of his thoughts: (1) the notion of right (subject matter of the science of philosophy of right) is a philosophical notion; (2) the right could be divided in terms of four features: origin, holder, correlation or the lack of correlation with inclusive or exclusive obligation; (3) all beings could have some rights; (4) God is the origin of all rights.